Peningkatan Pengelolaan Manajemen Sumberdaya Manusia Untuk Optimalisasi Kinerja Karyawan : Study Kasus CV. XXX - Budi Iriani Yudaningrum; Wiwit Setyo Wardani (JOURNAL KOPERASI DAN MANAJEMEN, 2023)
Purpose – The purpose of this essay is to evaluate how well human resource management affects employee performance. Organizational performance is the aggressiveness, or total, of all divisions’ performances, whereas divisional performance is the aggression of all members’ performances. Design/methodology/approach – The methodology in this study is qualitative. A qualitative approach is a research method that generates descriptive information from people’s spoken or written words and observed behavior. The purpose of this research is to describe and evaluate occurrences, events, and social interactions, as well as individual and group attitudes, beliefs, perceptions, and ideas. Findings – According to the study’s findings and the debate that followed, human resource management is crucial for enhancing employee performance in planning, hiring, selecting, and training new employees. Employee performance evaluation is a key component of human resource management’s planning for evaluating personnel. Making a responsible choice throughout the hiring process is necessary to subsequently be considered as an employment candidate. Employees do selection tasks in the next step to ensure that they fulfill the requirements and specifications in accordance with their foreign exchange. Research limitations/implications – The more subjective informants used in this study run the significant danger of lowering the impartiality of the research findings. The researcher’s personality will influence the research’s findings; hence, when you meet other researchers with various personalities, the findings may change. Originality/value – There is little question that the resources found inside the company, particularly people who actively participate as actors in attempts to attain organizational goals, have an impact on the achievement of organizational goals. An initial learning process or a debriefing of a skill or idea would be used to carry out training in this study, it was discovered, in order to boost employee performance.